Medical and Psychiatric Risk Factors for Dementia in Veterans with and without Traumatic Brain Injury (TBI): A Nationwide Cohort Study. (20th December 2022) - Gardner, Raquel C.; Barnes, Deborah E; Bahorik, Amber L; Li, Yixia; Peltz, Carrie; Yaffe, Kristine
Abstract: Background: Traumatic brain injury (TBI) is an important risk factor for dementia and is especially common among Veterans. It is unknown whether TBI exposure moderates the effect of other common medical/psychiatric comorbidities that are also important risk factors for dementia in Veterans. If treatable or preventable comorbidities are either especially common or risky in TBI‐exposed Veterans, then this may have important public health implications for dementia prevention. Method: We conducted a retrospective cohort study using the Nationwide Veterans Health Administrative inpatient and outpatient data (2001‐2019). We identified all Veterans age 55 years with prior TBI and without baseline dementia (N = 95, 139) and age/sex/race‐matched 1:2 with Veterans without prior TBI or baseline dementia (N = 190, 278). We compared prevalence of seven common medical/psychiatric comorbidities (hypertension, coronary artery disease (CAD), diabetes, cerebrovascular disease (CVD), epilepsy, depression, and post‐traumatic stress disorder (PTSD)) and associated risk of incident dementia among Veterans with versus without prior TBI. We tested for interaction of each comorbidity with TBI on risk of dementia. We calculated risk of dementia associated with each comorbidity using multivariable hazard ratios (adjusting for demographics and all other comorbidities) and Fine‐Grey competing risk of death. We estimated population attributable risk (PAR) of dementia due to each comorbidity. Result: All comorbidities were more prevalent among Veterans with TBI compared to those without TBI: hypertension +12.5%, CAD +13.6%, diabetes +7.9%, CVD +10.8%, epilepsy +5.7%, depression +21.5%, PTSD +14.9%). All comorbidities were associated with elevated risk for dementia among Veterans with and without TBI. However, there was a significant interaction with TBI such that point estimates were slightly lower among Veterans with TBI (adjusted HRs 1.02‐1.31) versus Veterans without TBI (adjusted HRs 1.03‐1.82). However, the overall PARs for dementia were higher in Veterans with versus without TBI for several comorbidities (depression 8.7% vs. 7.4%; hypertension 3.8% vs. 1.6%; CVD 3.7% vs. 2.0%; epilepsy 2.1% vs. 1.1%), due to their higher prevalence in Veterans with TBI. Conclusion: While treating or preventing medical/psychiatric comorbidities among all Veterans remains a high public health priority, targeting depression, hypertension, CVD, and epilepsy may be especially important for dementia risk reduction among Veterans with prior TBI.